IMPROVING PATIENT OUTCOMES AND TEAM-BASED CARE IN HOSPITALS IN: SAUDI ARABIA: - Fahad Nafel Saeed Alshamrani; Saad Shafi Alaklobi; Fatimah Ghanem Abdullah Alshahrani; Ali Abdullah Saeed Aldirani; Saad Mohammed Alsaluli; Mohammed Abdullah Alqarni; Maram Turki Mufareh Alshahrani; Mazhaih Nafel Saeed Alshamrani; Mohammed Shabbab Al Zhrani; Ahmed Ali Ahmed Alalyani; Mohammed Marii Mohammed Alqarni; Majed Bashir Al-Shammari; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Team-based care has emerged as a promising approach to enhance patient outcomes in healthcare settings, including Saudi Arabia. This review article aims to explore the impact of team-based care on patient outcomes in the Saudi Arabian healthcare system. The study synthesizes existing literature and evidence to provide insights into the benefits and challenges of implementing team-based care in Saudi Arabia. The review discusses the key components of effective team-based care models, such as interdisciplinary collaboration, communication, and shared decision-making, and their role in improving patient outcomes. Furthermore, it examines the cultural and organizational factors that may influence the successful implementation of teambased care in the Saudi Arabian context. The review also highlights the importance of leadership, training, and support for healthcare professionals to effectively work in a team-based care environment. Overall, this review contributes to the growing body of literature on team-based care and provides recommendations for policymakers and healthcare providers in Saudi Arabia to enhance patient outcomes through collaborative care approaches.